1989
DOI: 10.2118/15239-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulation of a Tight, Very-High-Temperature Gas-Condensate Well

Abstract: Summary. Well KAL-5, completed in the Moslavacka Gora formation of the Pannonian basin in Yugoslavia, was tested at a flow rate of 75 Mscf/D [2124 std m3/d] of gas and 2.8 B/D [0.45 m3/d] of condensate and at a last bottomhole pressure (BHP) of 1,083 psi [7.5 MPa]. Pretreatment evaluation determined a reservoir permeability in the 0.003- to 0.004-md range. The high formation temperature (354 deg. F [179 deg. C]) poses problems for most fracturing fluids. This paper presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Because of the low permeability and the wettability characteristics, it may take a long time to perform the cleanup; in some cases, as little as 10 to 15% of the water load could be recovered (Mahadevan and Sharma 2005;Penny et al 1983). Even when the problem of water blocking is not significant, the accumulation of condensate around the fracture face when the pressure falls below dewpoint pressure could result in a reduction in the gas production rate (Economides et al 1989;Sognesand 1991;Baig et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low permeability and the wettability characteristics, it may take a long time to perform the cleanup; in some cases, as little as 10 to 15% of the water load could be recovered (Mahadevan and Sharma 2005;Penny et al 1983). Even when the problem of water blocking is not significant, the accumulation of condensate around the fracture face when the pressure falls below dewpoint pressure could result in a reduction in the gas production rate (Economides et al 1989;Sognesand 1991;Baig et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many laboratory 5,6,11,12,33 theoretical 1,2,4,9-14 and field investigations 10, [15][16][17][18][19][20][21][22][23] have been conducted over the last forty years to try to understand condensate reservoir flow behavior. It has been found that, when reservoir pressure around a well drops below the dew point pressure, retrograde condensation occurs and three regions are created with different liquid saturations 14,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Pseudo critical temperature (Tpc) and pressure (Ppc) proposed by Elsharkawy et al, (2000), which developed for gas condensate reservoirs were also used to model two phase compressibility factor. Transient pressure test data from high temperature heavy gas condensate well was obtained from Economides et al, (1989) and utilized to generate the IPR curves. New IPRs covers effect of condensate blockage near wellbore region as an important factor in reducing well productivity (Behmanesh et al, 2017;Chen et al, 1995;Fevang and Whitson, 1996;Gondouin et al, 1967;Rahimzadeh et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(17) has been used to calculate pseudopressure function. This is because the well that was selected for this study is producing heavy condensate and is very high in temperature (Economides et al, 1989).…”
Section: Two Phase Pseudopressure Approachmentioning
confidence: 99%
See 1 more Smart Citation